PENGEMBANGAN BAHAN AJAR MATEMATIKA BERBASIS WEB DENGAN MENGGUNAKAN WORDPRESS - Saluky Saluky (EduMa: Mathematics education learning and teaching, 2016)
ABSTRACTWeb-based math teaching materials using Wordpress is an alternative teaching materials used by teachers in the learning process to give the material as well as the collaboration of students and teachers Online. The development of research aims to develop a Web-based math teaching materials using Wordpress for appropriate and effective use in learning. The method used is the subject of research and development with SMA X Cirebon. The results showed that Web-based math teaching materials using Wordpress developed valid and effective to use for students of class X. Web-based math teaching materials using WordPress gets very worthy of an expert assessment of material by 96% .In the Web effectively used by students visits from classical completeness value at 97% with an average value of 80.833 and received good response from the students to the use of that site by 79%. Based on the results, it can be concluded that the developed site got a very decent ratings from experts and effectively used in learning by high school students X Cirebon.Â Keywords: Wordpresss, Teaching Material